The role of dendritic cells and their immunometabolism in rheumatoid arthritis - Suwa, Yuichi; Nagafuchi, Yasuo; Yamada, Saeko; Fujio, Keishi (Frontiers in Immunology, 2023)
Dendritic cells (DCs) play crucial roles in the pathogenesis of rheumatoid arthritis (RA), a prototypic autoimmune disease characterized by chronic synovitis and joint destruction. Conventional dendritic cells (cDCs) with professional antigen-presenting functions are enriched in the RA synovium. In the synovium, the cDCs are activated and show both enhanced migratory capacities and T cell activation in comparison with peripheral blood cDCs. Plasmacytoid dendritic cells, another subtype of DCs capable of type I interferon production, are likely to be tolerogenic in RA. Monocyte-derived dendritic cells (moDCs), once called “inflammatory DCs”, are localized in the RA synovium, and they induce T-helper 17 cell expansion and enhanced proinflammatory cytokine production. Recent studies revealed that synovial proinflammatory hypoxic environments are linked to metabolic reprogramming. Activation of cDCs in the RA synovium is accompanied by enhanced glycolysis and anabolism. In sharp contrast, promoting catabolism can induce tolerogenic DCs from monocytes. Herein, we review recent studies that address the roles of DCs and their immunometabolic features in RA. Immunometabolism of DCs could be a potential therapeutic target in RA.